Gender Equality Implementation in Women’s Legal Cases in Religious Courts - Kania, Dede; Fatoni, Siti Nur; Kusmayanti, Hazar; Rahmanillah, Vienka (Universitas Muhammadiyah Purwokerto, 2025)
This article analyses the implementation of the Supreme Court Regulation Number 3 of 2017 concerning Guidelines for Trial of Cases Involving Women Facing Legal Challenges (which is then written as SC Reg. 3/2017) in Religious Affairs Courts. This regulation provides a guideline and serves as a reference point for judges which helps them to better understand and implement the principles of gender equality and non-discrimination in hearing and trying a case involving women. This study employs juridical-empirical approach method and purposive sampling as the data collection technique in interviewing several judges at multiple religious affairs courts in Java Island, as well as in literature review. The result of this study shows that judges at religious affairs courts have adopted Supreme Court Regulation Number 3 of 2017 (hereinafter, SC Reg. 3/2017), although in their practices, even after four years since the enactment, there still isn’t any consensus or shared views amongst judges in implementing matters such as post-divorce women’s rights, especially regarding verstek (in absentia) judgment. However, several religious affairs court judges have shown a good understanding of equality between men and women, indicated by judgments that favours women. Religious court judges in their ex officio capacity may grant rights to divorced wives, even if they are not requested.